1981
DOI: 10.1099/0022-1317-54-2-343
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the DNA Associated with Incomplete Particles of Adenovirus Type 2

Abstract: SUMMARYThe nature of the DNA in incomplete particles (IP) synthesized by adenovirus type 2 and the ts4 mutant which accumulates such particles were analysed by agarose gel electrophoresis, restriction endonuclease cleavage and blot hybridization techniques. IP DNA consisted of a heterogeneous population of subgenomic-size DNA (IPSD1) and smaller molecules ranging from about 1000 base pairs to 200 base pairs (IPSD2). IPSD 1 from ts4 was more heterogeneous than that from wildtype (wt), but both contained sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…In addition to the empty capsids that lack any DNA, two classes of assembly intermediates, called light and heavy, exist in virus-infected cells. The light assembly intermediates are associated with DNA fragments derived from the left end of viral genome (Daniell, 1976 ; Khittoo and Weber, 1981 ). Interestingly, the light intermediates range in density from 1.29 g/cm 3 (empty capsids) to 1.34 g/cm 3 (mature virions), with longer DNA fragments associated with the particles of higher densities (Tibbetts, 1977 ).…”
Section: Evidence For Sequential Assembly Of Advmentioning
confidence: 99%
“…In addition to the empty capsids that lack any DNA, two classes of assembly intermediates, called light and heavy, exist in virus-infected cells. The light assembly intermediates are associated with DNA fragments derived from the left end of viral genome (Daniell, 1976 ; Khittoo and Weber, 1981 ). Interestingly, the light intermediates range in density from 1.29 g/cm 3 (empty capsids) to 1.34 g/cm 3 (mature virions), with longer DNA fragments associated with the particles of higher densities (Tibbetts, 1977 ).…”
Section: Evidence For Sequential Assembly Of Advmentioning
confidence: 99%
“…In view of the findings of Hammarskjold & Winberg (1980), that packaging of Ad 16 DNA is dependent on a sequence at the left end of the genome, it is not surprising that the discrete fragments from IP contain only left end sequences. Tibbetts (1977) and Khittoo & Weber (1981) suggested that IP-containing left end fragments may be assembly intermediates whose unprotected DNA was digested during purification, leaving the left end sequences protected within the capsid. An alternative theory is that subgenomic fragments are generated in infected cells from both ends of the genome and that the left end fragments are selectively packaged (Daniell & Mullenbach, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…IP containing subgenomic DNA have been reported for a subgroup A adenovirus serotype 12 (Adl2) (Burlingham et al, 1974), subgroup B serotypes 3, 7 and 16 (Prage et al, 1972;Daniell, 1976;Hammarskjold et al, 1977;Tibbetts, 1977;Hammarskjold & Winberg, 1980) and subgroup C serotype 2 (Burlingham et al, 1974;Daniell, 1976;Khittoo & Weber, 1981). Group B adenoviruses produce large quantities of incomplete particles and analysis of the DNA by gel electrophoresis has shown that it is more heterogeneous in size than the DNA from IP of Ad2 (Daniell, 1976;Tibbetts, 1977;Hammarskjold & Winberg, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the late phase of infection, pulse-labelling experiments suggest that many of these proteins are first assembled into empty shell precursor particles called top components (TC) due to their light density in equilibrium gradients (Ishibashi & Maizel, 1974;Rosenwirth et al, 1974). Such particles contain proteins II, III, Ilia, IV, V, PVI, PVIII, IX and very little DNA (Edvardsson et al, 1976;Khittoo & Weber, 1977, 1981Persson et al, 1979). In addition to evidence from pulse-chase experiments, the following suggest that TC are precursors to complete virions: (i) several temperature-sensitive (ts) mutants (2ts4, 2ts112, 2tsl01, 5ts58) accumulate TC; (ii) TC contain precursor proteins (PVI, PVIII); (iii) the TC accumulated by some mutants can be chased into complete virions (Chee-Sheung & Ginsberg, 1982;D'Halluin et al, 1978).…”
mentioning
confidence: 99%